Active phase compensation technique for buried target extraction - Y.‐S. Cho; S. Jung; Y.‐S. Chung (Electronics Letters)
A novel method for buried target extraction, the active phase compensation technique is proposed. The range migration algorithm (RMA) is the conventional method for synthetic aperture radar (SAR) image reconstruction, but if targets exist in different media, identification of the target can be difficult because of losses and the significant reflection from the boundary face. In this regard, the matrix pencil method is utilised to actively find the boundary point and buried target responses. Then, the reflection effect can be eliminated, and range cells corresponding to estimated target responses can be compensated by applying newly created compensation functions. It improves the detection accuracy of buried targets. Finally, experimental results demonstrated that the proposed technique performs better than the classic RMA.